Constituents of essential oils from the leaves and twigs of Zanthoxylum avicennae (Lamk.) DC. Growing in limestone forest, northern Viet Nam - Nguyen Phuong Hanh; Tran Huy Thai; Nguyen Thi Hien; Nguyen Sinh Khang; Nguyen Quang Hung; Chu Thi Thu Ha; Nguyen Duc Thinh; Bui Van Thanh; Nguyen Quoc Binh; , Dinh Thi Thu Thuy; et al. (Vietnam Journal of Science and Technology, 2022)
Zanthoxylum avicennae (Lam.) DC. is a medicinal and aromatic plant, belong to the Zanthoxylum genus. The plant is found in some Asian contries, including Viet Nam. The various parts of this plant has been used to medicine and contain essential oils. In this study, the essential oil of Z. avicennae was isolated. Two essential oils from the leaves and twigs of Zanthoxylum avicennae (Lamk.) DC. collected from a limestone forest in Northern part of Vietnam were separately obtained by hydrodistillation and analyzed by GC-MS. A total of 42 and 53 compounds were identified in the leaf and twig oil, respectively. Mono- and sesquiterpenes were found to be the main chemical classes in both oils. Major constituents of the leaf oil were β-caryophyllene (18.71 %), α-humulene (14.03 %), α-terpinene (10.65 %), γ-terpinene (10.64 %), and linalool (9.42 %). Major constituents of the twig oil were linalool (18.3 %), β-phellandrene (8.82 %), α-terpinene (7.85 %), o-cymene (7.79 %), γ-terpinene (7.99 %), and (E)-β-ocimene (6.62 %). In the leaf oil the total amounts of mono- and sesquiterpenes were nearly equal (49.15 % and 44.27 %, respectively), while the twig oil was dominated by monoterpenes (76.66 % and 2.65 %, respectively). Previous literature data on essential oils obtained from this plant species were reviewed and discussed.